Sustainable Tourism Management for Enhanced Tourism Product Quality in the Cultural Village of Dokan - Sitorus, Nova Bernedeta; Liyushiana, Liyushiana; Khairi, Nurhafizhah (Jurnal Ilmiah Global Education, 2024)
The research on "Sustainable Tourism Management in Improving the Quality of Tourism Products in Dokan Cultural Village" encompasses several crucial objectives. First and foremost, it aims to identify the tourism potential of Dokan Cultural Village by examining its cultural richness, natural attractions, and other unique elements that draw tourists. Additionally, the study delves into the impact of tourism practices on the village’s environment, analyzing ecological sustainability, waste management, and natural resource conservation. Destination management is also a focal point, evaluating how policies and practices are implemented to ensure the sustainability, safety, and comfort of tourists. The research further explores community participation in tourism management, assessing decision-making involvement, economic empowerment, and the consideration of local communities’ needs. Identifying economic empowerment opportunities for local communities through the development of tourism products is another key objective, involving an analysis of local business potential and the role of community engagement in enhancing the value of tourism products. Central to the study is the evaluation and enhancement of the quality of tourism products in Dokan Cultural Village, encompassing service quality, diverse experiences, and the alignment with traveler expectations. Furthermore, the research aims to support sustainable tourism principles by identifying management practices that promote economic, social, and environmental sustainability. Ultimately, the study seeks to provide concrete recommendations for improving sustainable tourism management in Dokan Cultural Village, potentially including policy enhancements, the development of training programs, or the implementation of innovative destination management strategies. By achieving these objectives, the research aims to offer a comprehensive understanding of how Dokan Cultural Village can harness its potential as a sustainable tourism destination through the enhancement of its product quality.